1995
DOI: 10.1002/j.1460-2075.1995.tb00123.x
|View full text |Cite
|
Sign up to set email alerts
|

Negative feedback regulation of wild-type p53 biosynthesis.

Abstract: When growth‐arrested mouse fibroblasts re‐entered the cell‐cycle, the rise in tumour suppressor p53 mRNA level markedly preceded the rise in expression of the p53 protein. Furthermore, gamma‐irradiation of such cells led to a rapid increase in p53 protein biosynthesis even in the presence of the transcription inhibitor actinomycin D. Both findings strongly suggest that p53 biosynthesis in these cells is regulated at the translational level. We present evidence for an autoregulatory control of p53 expression by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
99
0
3

Year Published

1996
1996
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(107 citation statements)
references
References 42 publications
5
99
0
3
Order By: Relevance
“…Indeed, there is ample evidence for a functiondependent localization of p53 to either cellular compartment. When resting cells resume cycling, wt p53 remains in the cytoplasm during G1 phase, but is translocated into the nucleus at the onset of S-phase (Shaulsky et al, 1990a), in accordance with a role of wt p53 in translational control of its own mRNA in G1 (Mosner et al, 1995). During di erentiation of neurons and oligodendrocytes explanted from embryonic rat brain, wt p53 is translocated into the nucleus and is relocated to the cytoplasm in di erentiated cells (Eizenberg et al, 1996).…”
Section: Introductionmentioning
confidence: 66%
“…Indeed, there is ample evidence for a functiondependent localization of p53 to either cellular compartment. When resting cells resume cycling, wt p53 remains in the cytoplasm during G1 phase, but is translocated into the nucleus at the onset of S-phase (Shaulsky et al, 1990a), in accordance with a role of wt p53 in translational control of its own mRNA in G1 (Mosner et al, 1995). During di erentiation of neurons and oligodendrocytes explanted from embryonic rat brain, wt p53 is translocated into the nucleus and is relocated to the cytoplasm in di erentiated cells (Eizenberg et al, 1996).…”
Section: Introductionmentioning
confidence: 66%
“…Instability of mouse p53 in MCF7 is not due to inhibition of translation (Mosner et al, 1995) have demonstrated the inhibition of translation of p53 mRNA by wild-type p53 protein.…”
Section: Infection Of Mcf7 Cells With Sv40 Leads To Accumulation Of Pmentioning
confidence: 93%
“…This might be the mechanism for selection of mutant p53 cell clones which survive hypoxic stress and eventually colonise the tumour leading to malignancy. A novel mechanism which may relate to p53 induction has been described by Mosner et al (1995). They have demonstrated that wild-type p53 protein can inhibit the translation of its own messenger RNA by binding to a putative stem loop structure in the 5' untranslated region.…”
Section: Introductionmentioning
confidence: 99%
“…Mosner et al (1995) showed a negative feedback regulation of p53 on its own synthesis. The p53 mRNA can form a stable stemloop structure that involves the 5'-untranslated region (5'-UTR) as well as some 280 nucleotides of the coding sequence.…”
Section: Introductionmentioning
confidence: 97%